Molecular tracking of individual host use in the Shiny Cowbird – a generalist brood parasite - de la Colina, Ma Alicia (Ecol Evol, 2016)
Generalist parasites exploit multiple host species at the population level, but the individual parasite's strategy may be either itself a generalist or a specialist pattern of host species use. Here, we studied the relationship between host availability and host use in the individual parasitism patterns of the Shiny Cowbird Molothrus bonariensis, a generalist avian obligate brood parasite that parasitizes an extreme range of hosts. Using five microsatellite markers and an 1120‐bp fragment of the mtDNA control region, we reconstructed full‐sibling groups from 359 cowbird eggs and chicks found in nests of the two most frequent hosts in our study area, the Chalk‐browed Mockingbird Mimus saturninus and the House Wren Troglodytes aedon. We were able to infer the laying behavior of 17 different females a posteriori and found that they were mostly faithful to a particular laying area and host species along the entire reproductive season and did not avoid using previously parasitized nests (multiple parasitism) even when other nests were available for parasitism. Moreover, we found females using the same host nest more than once (repeated parasitism), which had not been previously reported for this species. We also found few females parasitizing more than one host species. The use of an alternative host was not related to the main hosts' nest availability. Overall, female shiny cowbirds use a spatially structured and host species specific approach for parasitism, but they do so nonexclusively, resulting in both detectable levels of multiple parasitism and generalism at the level of individual parasites.